Motivation, Anxiety, Life Satisfaction and Adherence in Spanish Adolescent Soccer Players - Carmen Galán-Arroyo; Santiago Gómez-Paniagua; Antonio Castillo-Paredes; Jorge Rojo-Ramos (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The global rise in sedentary lifestyles and deteriorating mental health among youth presents a significant concern. Sport motivation in young individuals is recognized as a catalyst for fostering a positive attitude towards regular physical activity and sports participation. However, anxiety contributes to a lack of motivation for engaging in these activities. Life satisfaction, a component of subjective well-being, in the context of sports, has the potential to enhance an individual's quality of life by offering a stabilizing activity that promotes achievement, success, and happiness. The primary objective of this study was to analyse the overall life satisfaction of young soccer players and to understand its impact on their emotional well-being and sporting performance, considering the motivational factors and anxiety that influence them. A descriptive cross-sectional study was conducted involving 495 young soccer players from Spain, aged 11 to 18 years. The sample comprised 285 boys and 210 girls, with a mean age of 15 years. Significant differences were observed across all items of the Satisfaction with Life Scale (SWLS) based on gender (with higher scores in boys) and academic cycle (with higher scores in the first cycle). On the State-Trait Anxiety Inventory (STAI), gender differences were noted in Trait Anxiety, which was higher in females. Additionally, significant differences were found in both State Anxiety and Trait Anxiety when considering the academic cycle, with second-cycle students exhibiting lower levels of anxiety. Regarding the dimensions of the Sport Motivation Scale/Emotional Measures of Development (SMS/EMD), significant differences were identified in intrinsic motivation, extrinsic motivation, and amotivation based on gender, with boys scoring higher than girls. In terms of demographic location, only intrinsic motivation for experiencing stimuli was higher in urban settings, while amotivation was more prevalent in rural areas. Cycle differences were observed solely in the intrinsic motivation dimension, favouring second-cycle students. Furthermore, an inverse correlation was noted between anxiety and amotivation, indicating that as anxiety and amotivation increase, life satisfaction tends to decrease. This research provides valuable insights into how anxiety and motivation influence the lives of young athletes. The findings indicate that increased demotivation and anxiety are associated with decreased life satisfaction among the subjects studied. This information can be instrumental for coaches and the broader environment of young athletes, enabling them to address these aspects effectively. By fostering a better understanding of the impact of anxiety and motivation, stakeholders can enhance athletes' mental health and ensure sustained adherence to sports, thereby promoting a high level of life satisfaction.